Controlling grain nucleation and morphology by laser beam shaping in metal additive manufacturing. (October 2020) - Roehling, Tien T.; Shi, Rongpei; Khairallah, Saad A.; Roehling, John D.; Guss, Gabe M.; McKeown, Joseph T.; Matthews, Manyalibo J.
Abstract: Gaussian laser intensity profiles are standard in laser-based metal additive manufacturing, although recent work in single-layer melt tracks showed that beam shaping could offer a feasible route towards microstructural control. Since thermal cycling and grain orientation templating in multilayer builds can alter microstructures, we compare three-dimensional 316 L stainless steel cubes built using Gaussian and elliptical laser intensity profiles. Microstructural characterization confirms that elliptical beams result in a modified and improved microstructure compared to Gaussian beams. This assessment favoring the elliptical beam is based on: (1) the observed refinement of the columnar and equiaxed grains; (2) more importantly, the volume fraction occupied by equiaxed grains increases dramatically such that the average grain area is reduced by nearly 50%; (3) reduced texture in cubes built using an elliptical beam. The random orientation of small equiaxed grains in samples built using an elliptical beam also suggests a higher nucleation frequency. High-fidelity finite element simulations that deliver accurate thermal profiles by incorporating laser ray tracing and fluid dynamics were performed. Using a time-dependent solidification map based on local thermal gradients ( G ) and growth rates ( R ), our simulation results confirm the experimentally observed trend that an elliptical beam results in a favorable thermal profile. Graphical abstract: Unlabelled Image Highlights: Starkly different 316 L microstructures were built by laser AM using circular Gaussian and elliptical laser beams With a higher area fraction occupied by equiaxed grains, the average grain area decreased by ~50% using the elliptical beam Randomly oriented small grains formed using the elliptical beam suggest a higher nucleation frequency Overall crystallographic texture was reduced using the elliptical beam